Indications for percutaneous left atrial appendage occlusion in hospitalized patients with atrial fibrillation. Issue 3 (March 2022) - Vrana, Eleni; Kartas, Anastasios; Samaras, Athanasios; Vasdeki, Dimitra; Forozidou, Evropi; Liampas, Evangelos; Karvounis, Haralambos; Giannakoulas, George; Tzikas, Apostolos
Abstract : Aims: Percutaneous left atrial appendage occlusion (LAAO) is an alternative nonpharmacological therapeutic option for stroke prevention in patients with NVAF. However, no data exist on potential LAAO candidates' prevalence among 'real-world' NVAF patients. This study aimed to investigate the indications for LAAO in hospitalized patients with comorbid nonvalvular atrial fibrillation (NVAF). Methods: This is a post-hoc analysis of the MISOAC-AF (Motivational Interviewing to Support OAC-AF, ClinicalTrials.gov: NCT02941978), randomized controlled trial, which enrolled NVAF patients hospitalized for any reason in a tertiary cardiology department. In this analysis, patients with a history of major bleeding or stroke under OAC therapy were considered to have a strong indication for LAAO. Results: A total of 980 patients with NVAF were studied (mean age 73.9 ± 10.9 years, 54.7% men). Prior major bleeding occurred in 134 (13.7%) patients (intracranial bleeding in 1%, upper and lower gastrointestinal bleeding in 6.4 and 8.9%, respectively). A total of 58 (5.9%) patients experienced an embolic stroke while being treated using OAC. Overall, either of these events was prevalent in 173 (17.7%) patients, denoting a strong indication for LAAO. Conclusion: Almost one out of six patients hospitalized with comorbid NVAF may be considered eligible for percutaneous LAAO for stroke prevention. Trial Identification: NCT02941978, https://clinicaltrials.gov/ct2/show/NCT02941978 .